3D-printed collagen/silk fibroin/secretome derived from bFGF-pretreated HUCMSCs scaffolds enhanced therapeutic ability in canines traumatic brain injury model - Liu, Xiaoyin; Zhang, Guijun; Wei, Pan; Hao, Lifang; Zhong, Lin; Zhong, Kunhon; Liu, Chang; Liu, Peng; Feng, Qingbo; Wang, Shan; Zhang, Jianyong; Tian, Rui; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
The regeneration of brain tissue poses a great challenge because of the limited self-regenerative capabilities of neurons after traumatic brain injury (TBI). For this purpose, 3D-printed collagen/silk fibroin/secretome derived from human umbilical cord blood mesenchymal stem cells (HUCMSCs) pretreated with bFGF scaffolds (3D-CS-bFGF-ST) at a low temperature were prepared in this study. From an in vitro perspective, 3D-CS-bFGF-ST showed good biodegradation, appropriate mechanical properties, and good biocompatibility. In regard to vivo, during the tissue remodelling processes of TBI, the regeneration of brain tissues was obviously faster in the 3D-CS-bFGF-ST group than in the other two groups (3D-printed collagen/silk fibroin/secretome derived from human umbilical cord blood mesenchymal stem cells (3D-CS-ST) group and TBI group) by motor assay, histological analysis, and immunofluorescence assay. Satisfactory regeneration was achieved in the two 3D-printed scaffold-based groups at 6 months postsurgery, while the 3D-CS-bFGF-ST group showed a better outcome than the 3D-CS-ST group.